Structural Content in Paintings: Artists Overregularize Oriented Content of Paintings Relative to the Typical Natural Scene Bias. (December 2013) - Schweinhart, April M; Essock, Edward A
Natural scenes tend to be biased in both scale (1/ f ) and orientation (H > V ≫ O; horizontal > vertical ≫ oblique), and the human visual system has similar biases that serve to partially 'undo' (ie whiten) the resultant representation. The present approach to investigating this relationship considers content in works of art—scenes produced for processing by the human visual system. We analyzed the content of images by a method that minimizes errors inherent in some prior analysis methods. In the first experiment museum paintings were considered by comparing the amplitude spectrum of landscape paintings, natural scene photos, portrait paintings, and photos of faces. In the second experiment we obtained photos of paintings at the time they were produced by local artists and compared structural content in matched photos which contained the same scenes that the artists had painted. Results show that artists produce paintings with both the 1/ f bias of scale and the horizontal effect bias of orientation (H > V ≫ O). More importantly, results from both experiments show that artists over regularize the structure in their works: They impose the natural-scene horizontal effect at all structural scales and in all types of subject matter even though, in the real world, the pattern of anisotropy differs considerably across spatial scale and between faces and natural scenes. It appears that artists unconsciously overregularize the oriented structure in their works to make it conform more uniformly to the 'expected' canonical ideal.